Cybercrime: digital cops in a networked environment ; the information society project at Yale Law School - Balkin, Jack M. (Ex machina, 2007)
The physics of digital law : searching for counterintuitive analogies / Daniel E. Geer, Jr. -- Architectural regulation and the evolution of social norms / Lee Tien -- Where computer security meets national security / Helen Nissenbaum -- Real world problems of virtual crime / Beryl Howell -- Designing accountable policing / Nimrod Kozlovski -- Counterstrike / Curtis E.A. Karnow -- Why can't we all get along? : how technology, security, and privacy can co-exist in the digital age / Kim A. Taipale -- Calea : does one size still fit all? / Stewart A. Baker and Emily Hancock -- The Council of Europe's convention on cybercrime / Susan W. Brenner -- Digital evidence and the new criminal procedure / Orin S. Kerr